Post-drought Resilience After Forest Die-Off: Shifts in Regeneration, Composition, Growth and Productivity - Gazol, Antonio; Camarero, J. Julio; Sangüesa-Barreda, Gabriel; Vicente-Serrano, Sergio M. (Frontiers in Plant Science, 2018)
A better understanding on the consequences of drought on forests can be reached by paying special attention to their resilience capacity, i.e., the ability to return to a state similar to pre-drought conditions. Nevertheless, extreme droughts may surpass the threshold for the resilience capacity triggering die-off causing multiple changes at varying spatial and temporal scales and affecting diverse processes (tree growth and regeneration, ecosystem productivity). Combining several methodological tools allows reaching a comprehensive characterization of post-drought forest resilience. We evaluated the changes in the abundance, regeneration capacity (seedling abundance), and radial growth (annual tree rings) of the main tree species. We also assessed if drought-induced reductions in growth and regeneration of the dominant tree species scale-up to drops in vegetation productivity by using the Normalized Difference Vegetation Index (NDVI). We studied two conifer forests located in north-eastern Spain which displayed drought-induced die-off during the last decades: a Scots pine (Pinus sylvestris) forest under continental Mediterranean conditions and a Silver fir (Abies alba) forest under more temperate conditions. We found a strong negative impact of a recent severe drought (2012) on Scots pine growth, whereas the coexisting Juniperus thurifera showed positive trends in basal area increment (0.02 ± 0.003 cm2 yr-1). No Scots pine recruitment was observed in sites with intense die-off, but J. thurifera and Quercus ilex recruited. The 2012 drought event translated into a strong NDVI reduction (32% lower than the 1982–2014 average). In Silver fir we found a negative impact of the 2012 drought on short-term radial growth, whilst long-term growth of Silver fir and the coexisting Fagus sylvatica showed positive trends. Growth rates were higher in F. sylvatica (0.04 ± 0.003 cm2 yr-1) than in A. alba (0.02 ± 0.004 cm2 yr-1). These two species recruited beneath declining and non-declining Silver fir trees. The 2012 drought translated into a strong NDVI reduction which lasted until 2013. The results presented here suggest two different post-drought vegetation pathways. In the Scots pine forest, the higher growth and recruitment rates of J. thurifera correspond to a vegetation shift where Scots pine is being replaced by the drought-tolerant juniper. Conversely, in the Silver fir forest there is an increase of F. sylvatica growth and abundance but no local extinction of the Silver fir. Further research is required to monitor the evolution of these forests in the forthcoming years to illustrate the cumulative impacts of drought on successional dynamics.